Differentiating the Level of the School Leaders’ Positive Traits Anchored on Appreciative Inquiry Attributes: Inputs to Improving Teachers’ Collaboration and the School-Based Management Level (American Journal of Multidisciplinary Research and Innovation, 2022)
This study used Quantitative, evaluative, and descriptive research designs to determine the school leaders’ Appreciative Inquiry (AI) level of practice and which among the AI practices predict improvements in the school leaders’ collaboration that can be used in crafting AI strategies. One-Way Analysis of Variance, Pearson-Product-Moment Correlation, and Multiple Regression were used in this study. The researcher made-questionnaires were administered to the 157 school leaders that were grouped based on their administrative function. The findings were articulated based on the data gathered and the analysis made: 1. School heads had the lowest AI level among the school leaders, but they were found to have the highest perception results when it comes to the SBM components practices; 2. there was a low to moderate positive correlation among all the variables related to SBM components and the school leaders’ AI level practices in terms of discovery, dream, design, and destiny; 3. the SBM components variables were found to be “very important” and contributory factor to a higher SBM level. 4. Among the phases of AI, Design and Destiny predict high collaboration in which, for every one (1) unit increase in the school and school leader’s AI level, there was a corresponding increase in the SBM performance. It was concluded that school heads may set good examples as AI practitioners to effectively promote collaboration. Schools may use the suggested strategies as they are anchored on the best practices of the school leaders and are found to be predictors of high SBM performance.